Model Operasional Pelatihan Pada Balai Latihan Kerja Tasikmalaya dalam Menyiapkan Tenaga Kerja Profesional - Hilmi Nur Fakhira; Yus Darusman (Lifelong Education Journal, 2022)
According to the Central Statistics Agency, the unemployment rate in Tasikmalaya City and Regency is quite high, so one solution is through training at the Job Training Center by preparing a professional workforce. For the successful implementation of a training, it is necessary to use a training model. The purpose of this study is to find out how the operational model of training at the Tasikmalaya Job Training Center in preparing a professional workforce. The research method used is descriptive qualitative, the type of data collection in this study is through observation, interviews, and documentation. The research instrument used was through observation and interview guidelines. Technical data analysis uses several stages such as data reduction, data presentation, and drawing conclusions. The results of this study are the operational training model used by the Tasikmalaya Job Training Center in preparing a professional workforce, namely the Competency-Based Training Model (PBK) which means job training that will focus on the final result (Outcome). After attending the training, participants are expected to become competent and professional workers. Types of training include Institutional Training which is carried out at the Office of the Job Training Center and Mobile Training Unit (MTU) which is carried out at the residence of local residents. With the following steps: Identification of Training Needs which aims to see and determine what training will be held according to the needs of the training participants, Designing Training Programs such as making curriculum, materials, schedules and preparing props needed, Implementing Training Programs by selecting students prospective trainees and Conduct Training Evaluations in the form of vocational evaluations and program evaluations. Keywords: Training Operational Model, Job Training Center